Modelamiento y simulación de redes de telecomunicación para medición inteligente de energía eléctrica residencial en zonas urbanas - Suárez Pozo, Carlos Guillermo (2015)
This thesis project allows us to analyze the behavior of the telecommunications network in urban areas; and thus warn the needed infrastructure to implement smart metering of electricity. To this end, a mathematical optimization model to minimize distances was raised as a method to cluster-unite devices (smart meters) within an urban area cellular coverage. For this, modeling must be adapted to the behavior of the cellular network, so that facilitates us to minimize the economic impact by implementing smart metering from scratch. Smart metering devices shall assume the sending and receiving data over cellular networks offered by operators of advanced mobile services which may be present in the same primary dealer or reducing infrastructure costs in a secondary operator through leasing. Due to the nature of these communications infrastructure is important to consider that an urban area involve determinants factors for data transfer behavior; for this reason, the network behavior parameters based on base station and smart meters transmission power, channel assignment and simulator propagation models are simulated.